ChemInform Abstract: Scalarane Sesterterpenes from the Egyptian Red Sea Sponge Phyllospongia lamellosa. Issue 22 (15th May 2015) - Hassan, Marwa H. A.; Rateb, Mostafa E.; Hetta, Mona; Abdelaziz, Tarek A.; Sleim, Mohamed A.; Jaspars, Marcel; Mohammed, Rabab
Abstract: Five new scalarane sesterterpenes, phyllospongins A‐E (I)‐(III) are isolated along with four known derivatives from the dichloromethane fraction of the marine sponge Phyllospongia lamellosa.